The "Kansas City" approach to modern money theory - Larry Randall Wray (Levy Economics Institute of Bard College, 2020)
Modern money theory (MMT) synthesizes several traditions from heterodox economics. Its focus is on describing monetary and fiscal operations in nations that issue a sovereign currency. As such, it applies Georg Friedrich Knapp's state money approach (chartalism), also adopted by John Maynard Keynes in his Treatise on Money. MMT emphasizes the difference between a sovereign currency issuer and a sovereign currency user with respect to issues such as fiscal and monetary policy space, ability to make all payments as they come due, credit worthiness, and insolvency. Following A. Mitchell Innes, however, MMT acknowledges some similarities between sovereign and nonsovereign issues of liabilities, and hence integrates a credit theory of money (or, "endogenous money theory," as it is usually termed by post-Keynesians) with state money theory. MMT uses this integration in policy analysis to address issues such as exchange rate regimes, full employment policy, financial and economic stability, and the current challenges facing modern economies: rising inequality, climate change, aging of the population, tendency toward secular stagnation, and uneven development. This paper will focus on the development of the "Kansas City" approach to MMT at the University of Missouri-Kansas City (UMKC) and the Levy Economics Institute of Bard College.
Keywords: B1; B2; B52; E12; E5; 330; Modern Money Theory (MMT); Functional Finance; Chartalism; State Theory of Money; Sectoral Balances; Kansas City Approach; Job Guarantee; Sovereign Currency